Students' preferred teaching techniques for biochemistry in biomedicine and medicine courses - Novelli, Ethel L. B. [UNESP]; Fernandes, Ana Angélica H. [UNESP] (Wiley, 2007)
The aim of this study was to investigate the students' preferred teaching techniques, such as traditional blackboard, power-point, or slide-projection, for biochemistry discipline in biomedicine and medicine courses from São Paulo State University, UNESP, Botucatu, São Paulo, Brazil. Preferences for specific topic and teaching techniques were determined from questionnaires on a Liquert scale from 1 to 5 (strongly disagree; disagree; neither agree, nor disagree; agree; strongly agree) distributed at the end of biochemistry discipline to 180 biomedical students (30 students/year) and 540 medical students (90 students/year), during the years 2000-2005. Despite of the different number of hours applied to the course topics for the two groups of students, the majority of undergraduates from biomedicine and medicine preferred metabolic topics. Although the perception of a medical student is expected to be different than that of a biomedical student, as the aims of the two programs are different, 92.4% of students from each course agreed or strongly agreed with the biochemistry topics, and 92.1% thought highly on this subject. The majority of students, a number of 139 undergraduates from biomedicine and 419 from medicine course, preferred traditional blackboard teaching than slide-projection, or power-point class. In conclusion, it is imperative that the health courses reflect on sophisticated technology and data presentation with high density of information in biochemistry discipline. The traditional classes with blackboard presentation were most favored by students from biomedicine and medicine courses. The use of students' preferred teaching techniques might turn biochemistry more easily understood for biomedical and medical students. © 2007 by The International Union of Biochemistry and Molecular Biology.
Keywords: Biochemistry; Healthy courses; Teaching techniques; biochemistry; biomedicine; Brazil; education program; medical education; medical student; questionnaire; rating scale; student; teaching; university